ANALISIS KUALITAS KERUPUK KULIT UDANG - Dinda, Viola Karina; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aims to analyze the influence of the quality of the use of shrimp skin as much as 55%, 70%, 85% and 100% of the quality cracker in terms of quality of form, color, aroma, texture, and taste. This type of research purely experiments (true experimental) using the method of complete random design of one factor, namely the use of shrimp skin three times iteration. The type of the data being used is the primary and secondary data sourced from 30 panelists who gave the answer of question form (format organoleptic). The data already acquired later in the tabulated in the form of tables and done the analysis Variant (ANAVA). If different real continued with test Duncan. Results of the research showed there were significant effects on quality of skin shrimp crackers on the quality of the color beige brownish and savory. While the quality of the form (uniform and neat), scent and texture of crunchy had no effect on quality of skin cracker shrimp. Best is present on the percentage of use of shrimp skin as much as 100%.Keywords: Shrimp Skin, Crackers, Quality